2018
DOI: 10.4103/psychiatry.indianjpsychiatry_107_17
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference between attitude of interns toward psychiatric illness and other chronic medical conditions? A comparative study

Abstract: Background:Attitude of doctors towards specific medical conditions plays a crucial role in patient care. Internship, being the final stage in undergraduate medical students’ training, can have a bearing on the attitude they develop towards various specialties. However, there is dearth of Indian studies comparing the attitude of interns towards psychiatric illness and other chronic medical conditions. In this background, the study was conceived with the objective of comparing the attitude of interns towards psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Two other studies found poor levels of knowledge, with one study showing that 53.7% of students had poor knowledge regarding preventive measures of suicidal behaviour [ 95 ] and another showing that 43% of school students had inadequate knowledge of substance use [ 96 ]. Another study found that medical interns agreed that ‘patients like this (with psychiatric illnesses) irritate me’ or treating them was a ‘waste of money.’ [ 97 ] A qualitative study echoed our findings that mental health and mental illness were unclear concepts and were associated with acute problems, such as ‘brain deficiency or dysfunction and abnormal behaviour.’ [ 98 ] Another qualitative study found that college students believed that using substances helped to relieve depression, enhance health and lose weight and that using in small quantities did not cause harm [ 99 ]. The study suggests that future interventions should be non-judgemental, student-friendly, relatable and ‘specific to the youth’s life circumstances and needs.’…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Two other studies found poor levels of knowledge, with one study showing that 53.7% of students had poor knowledge regarding preventive measures of suicidal behaviour [ 95 ] and another showing that 43% of school students had inadequate knowledge of substance use [ 96 ]. Another study found that medical interns agreed that ‘patients like this (with psychiatric illnesses) irritate me’ or treating them was a ‘waste of money.’ [ 97 ] A qualitative study echoed our findings that mental health and mental illness were unclear concepts and were associated with acute problems, such as ‘brain deficiency or dysfunction and abnormal behaviour.’ [ 98 ] Another qualitative study found that college students believed that using substances helped to relieve depression, enhance health and lose weight and that using in small quantities did not cause harm [ 99 ]. The study suggests that future interventions should be non-judgemental, student-friendly, relatable and ‘specific to the youth’s life circumstances and needs.’…”
Section: Discussionmentioning
confidence: 61%
“…Another study found that medical interns agreed that 'patients like this (with psychiatric illnesses) irritate me' or treating them was a 'waste of money.' [97] A qualitative study echoed our findings that mental health and mental illness were unclear concepts and were associated with acute problems, such as 'brain deficiency or dysfunction and abnormal behaviour.' [98] Another qualitative study found that college students believed that using substances helped to relieve depression, enhance health and lose weight and that using in small quantities did not cause harm [99].…”
Section: Strengths and Limitationsmentioning
confidence: 58%
“…In accordance with the present results, previous studies had demonstrated that medical and nursing students had reflected positive and acceptance attitudes towards mental illness. [1,26,27] In addition, physiotherapy students showed favorable attitudes towards mental illness. [12,13] In contrast to earlier findings, medical students illustrated negative attitudes toward mental illness [2,4,17] This inconsistency may be due to many reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an intern can detect hypoglycemia for the first time when measuring a patient’s blood sugar. If nursing interns know how to deal with hypoglycemic events, they can instruct patients to eat the correct glucose-increasing food immediately, thereby reducing the time interval from discovery to treatment of hypoglycemia and reducing the occurrence of adverse events [ 8 ].…”
Section: Introductionmentioning
confidence: 99%